BUDAYA ORGANISASI DAN AKTIVITAS DAKWAH - Ahmad Yasser mansyur; Ahmad Razak (Jurnal Psikologi TALENTA, 2015)
This study aimed to examine the influence of Muhammadiyah organization’s culture against cultural dakwah activities carried out by the teachers. Demographic aspects included to be tested to determine the difference in the variables studied. This was a population research, the subject of research were the teachers with Muballigh status at the Twigs and Branches levels of Muhammadiyah Tello Baru Makassar amounted of 44 peoples. Two measuring devices used to collect information about the variables studied, the scale of the organization's culture and dakwah. Technique used to analyze the data were simple regression and T test. The results showed that the organization’s culture affected the cultural propaganda significantly (F (1,42) = 39.189, p <.05), with 48.3 percent of variants donations. From demography aspect, based on sex, showed no differences in organization’s culture and dakwah.